High-Performance Organic Electric Double-Layer Capacitors Using Allergen-Derived Activated Carbons. Issue 16 (1st January 2019) - Yang, Inchan; Yoo, Jihoon; Lee, Joohyung; Kim, Myung-Soo; Jung, Ji Chul
Abstract : In this study, an allergen (pollen) is converted into a carbon electrode material for organic electric double-layer capacitors. Pollen is applied to electrodes by carbonization and activating it with gas or chemical agents. The carbonization is conducted at 800°C under flowing nitrogen, and the activation is subsequently performed at different temperatures between 700°C and 900°C. Then, using the prepared electrode materials, electric double-layer capacitors are fabricated. Particularly, an activated carbon activated at 900°C with potassium hydroxide, demonstrating electrochemical properties that are superior to the other electrode materials because of its large surface area and high electrical conductivity. The large surface area is due to its abundant micropores formed by the oxidation of non-graphitizable parts, while the high electrical conductivity results from that the portion of micropores are collapsed and graphitized. As electrode materials for electric double-layer capacitors, moreover, activated pollen carbons display better electrochemical properties compared with commercially-available activated carbon. In conclusion, pollen appears to have significant potential as an electrode material for low cost commercial electric double-layer capacitors, which are eco-friendly and display an excellent electrochemical performance. Herein, an activation mechanism for synthesizing the activated carbon is additionally proposed.